Advances in accounting behavioral research. Vol. 15 - Schmitt, Donna Bobek (Emerald, 2012)
Advances in Accounting Behavioral Research publishes high-quality behavioral research in all areas of accounting including financial, auditing, taxation, managerial, and information systems. This volume focuses on research that examines both individual and organizational behavior relative to accounting.
Keywords: Accounting -- Research.; elektronické knihy; electronic books